Quality Management of Islamic Religious Education Learning At State Madrasah Aliyah (Man) 1 Tangerang - Aris Setyawan (The International Journal of Education Management and Sociology, 2025)
This study aims to examine how quality management contributes to enhancing learning at madrasahs, as well as identifying the factors that support and hinder this process. The research employs a qualitative approach, focusing on data collected through written or spoken words from individuals involved in the observation process. The primary data sources for this study include the head of MAN 1 Tangerang, curriculum staff, teachers, and students. Data collection was carried out through interviews, observations, and document analysis. The findings reveal that the leadership of the madrasah head at MAN 1 Tangerang has effectively managed the improvement of Islamic Religious Education (PAI) quality across several key areas. These areas include the curriculum, teaching programs, educational staff, student engagement, financing, infrastructure, special services, and the relationship between the madrasah and the community, all contributing to a conducive learning environment. Based on the results, the following recommendations are offered for MAN 1 Tangerang: It is essential for the teaching staff, particularly those involved in PAI, to enhance their understanding of management principles to further improve the quality of Islamic Religious Education at the madrasah. The current implementation of management by the madrasah head has not yet fully optimized the teachers' work ethic. Several inhibiting factors, including teachers who are assigned to multiple madrasahs, contribute to a lack of focus and effectiveness in their work.